New Formula for Predicting Mean Pulmonary Artery Pressure Using Systolic Pulmonary Artery Pressure - Chemla, Denis; Castelain, Vincent; Humbert, Marc; Hébert, Jean-Louis; Simonneau, Gérald; Lecarpentier, Yves; Hervé, Philippe (Chest, 2004)
Mean pulmonary artery pressure (MPAP) and systolic pulmonary artery pressure (SPAP) are used interchangeably to define pulmonary hypertension (PH). We tested the hypothesis that the measurement of MPAP and SPAP is redundant in resting humans over a wide pressure range. Prospective, observational study. Catheterization laboratory in a university hospital. This study involved 31 patients, as follows: primary PH, nine patients; chronic pulmonary thromboembolism, seven patients; venous PH, six patients; and control subjects with normal pulmonary artery pressure, nine patients. None. High-fidelity pulmonary artery pressures were obtained when patients were at rest. Over the wide MPAP range that was under study (10 to 78 mm Hg), MPAP and SPAP were strongly related (r2 = 0.98). Regression analysis performed on the first 16 subjects (test sample) allowed us to propose a formula (MPAP = 0.61 SPAP + 2 mm Hg), the accuracy of which was confirmed in the remaining 15 subjects (validation sample bias, 0 ± 2 mm Hg). If PH was defined by an SPAP in excess of 30 or 40 mm Hg, this corresponded to an MPAP in excess of 20 or 26 mm Hg. If PH was defined by an MPAP of > 25 mm Hg, this corresponded to an SPAP of > 38 mm Hg. In resting humans, MPAP can be accurately predicted from SPAP over a wide pressure range. The new formula may help to refine the threshold pressure values used in the diagnosis of PH. Further studies are needed to test the hypothesis that our formula may allow the noninvasive prediction of MPAP from Doppler-derived SPAP values.